Ambidextrous Leadership as a Catalyst for Innovation Performance: Knowledge Sharing and Organizational Agility in Indonesian Digital SMEs - Faizal Faizal; Ivon Arisanti; Frandyo Izak Muskita (Eastasouth Institute, 2026)
This study examines the effect of ambidextrous leadership on innovation performance through knowledge sharing and organizational agility among digital small and medium-sized enterprises (SMEs) in Indonesia. The study is grounded in the Resource-Based View, which positions leadership, knowledge, and agility as strategic organizational capabilities for achieving competitive advantage. A quantitative research design was employed using data collected from 150 owners, managers, supervisors, and employees of Indonesian digital SMEs. Respondents were selected through purposive sampling, and the research variables were measured using a five-point Likert scale. Data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS 3. The results indicate that ambidextrous leadership has positive and significant effects on knowledge sharing, organizational agility, and innovation performance. Knowledge sharing also positively affects organizational agility and innovation performance, while organizational agility has the strongest direct effect on innovation performance. The structural model explains 46.5% of the variance in knowledge sharing, 61.3% of the variance in organizational agility, and 70.4% of the variance in innovation performance. Mediation analysis demonstrates that knowledge sharing and organizational agility partially mediate the relationship between ambidextrous leadership and innovation performance. These findings show that ambidextrous leaders improve innovation outcomes by balancing exploratory and exploitative leadership behaviors, promoting knowledge exchange, and strengthening organizational responsiveness. The study contributes to leadership and innovation literature by providing empirical evidence from Indonesian digital SMEs. Digital SME leaders are advised to encourage experimentation, maintain execution discipline, establish collaborative knowledge-sharing mechanisms, and develop flexible organizational processes to achieve sustainable innovation performance in dynamic digital markets.